P–328 Dienogest significantly decreases the size of the cyst and alters Anti-Müllerian Hormone concentration in patients with endometrioma. (6th August 2021) - Karataş, E; Temiz, B E; Mumusoglu, S; Yarali, H; Bozdag, G
Abstract: Study question: Does utilization of dienogest make any impact on the size of cyst and Anti-Müllerian Hormone (AMH) concentration in patients with endometrioma throughout 12-months? Summary answer: Although dienogest makes a gradual reduction in the size of endometrioma cyst throughout 12-months, a significant drop in AMH serum concentration was also noticed. What is known already: According to recent studies, pre-operative serum AMH levels might be illusively increased with parallel to the size of endometrioma which will be a misleading factor while deciding to operate the patient via cystectomy. Although dienogest is one of the medical options that might be commenced in patients with endometrioma cyst, there is limited data about its effect on the size of the endometrioma and hence serum AMH concentration throughout 12 months of follow up. Study design, size, duration: The current observational cohort study was conducted among patients with endometrioma those treated with dienogest from January 2017 to January 2020. The primary outcome was alteration in diameter of endometrioma cyst at 6th and 12th months of treatment. Secondary outcome was alteration in serum AMH concentration in the same period. Of 104 patients treated with dienogest, 44 patients were excluded due to being treated with any type of surgical intervention during follow up period. Participants/materials, setting, methods: A total of 60 patients were recruited for the final analysis. Of them, primary symptom was dysmenorrhea, chronic pelvic pain and menstrual irregularity in 16 (26.7%), 25 (41.7%) and 8 (13.3%) patients, respectively. Eighteen patients (30%) were asymptomatic. As 21 patients had bi-lateral endometrioma, size of the leading cyst was considered to be analyzed for the primary outcome measure. Paired-t test was used for comparison of numerical values and p ≤ 0.05 was taken as statistical significance. Main results and the role of chance: The mean age was 31.5±8.0 years. In the time point when dienogest was started, the mean size of the endometrioma was 46.3±17.4 mm. The mean serum AMH concentration was 3.6±2.4 ng/ml. After 6 months of treatment, the mean size of the endometrioma decreased to 38.6±14.0 mm which corresponds to a mean difference of 7.8 mm (95% CI: 3.0 to 12.6; p: 0.003). The respective figure for AMH was 3.3±2.7 ng/ml which corresponds to a mean difference of 0.3 ng/ml (95% CI: –0.2 to 0.8; p: 0.23) at 6 months. After 12 months of treatment, the mean size of the endometrioma was 37.5±15.7 mm which corresponds to a mean difference of 8.9 mm (95% CI: 2.9 to 14.9; p: 0.005) at the end of 12 months. The respective figure for AMH was 2.7±1.9 ng/ml which corresponds to a mean difference of 0.9 ng/ml (95% CI: 0.1 to 1.7; p: 0.045) at the end of 12 months. The mean diameter of endometrioma and AMH concentration did not differ throughout the time period between 6th and 12th months of the treatment. Limitations, reasons for caution: Although herein we present the largest data that depicts the alteration of endometrioma cyst and AMH concentration with the application of dienogest, the lack of control group is a limitation that avoids to perform any comparison. Wider implications of the findings: A shrinkage after commencement of treatment suggest that dienogest might present improvement in patients with endometrioma with respect to radiological findings, but further studies are required whether a decline in AMH concentration after 12 months refers to a genuine decrease in ovarian reserve or resolution of misleading high pre-treatment levels. Trial registration number: not available